Prevalence of thyroid dysfunction in women with abnormal uterine bleeding in reproductive age - R., Hema K.; L., Girish B.; S., Dhananjaya B.; Kalaburgi, Riyaj Ahmad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) is one of the commonest presentations encountered in gynecological outpatient department. Menstruation is also regulated by many mechanisms, including thyroid hormone. So, for definitive management of AUB, it becomes imperative to assess thyroid status in those with abnormal uterine bleeding. Methods: Cross sectional study was conducted on all woman attending to OPD at Sri Siddhartha Medical College, Tumukuru, with complaints of abnormal uterine bleeding (AUB). Thyroid test was done for those who were eligible under inclusion criteria. Incidence of thyroid disorders among AUB and type of abnormal menstrual pattern associated with specific type of thyroid dysfunction were noted in this study. Results: Total of 522 presented with AUB. AUB was most common among woman age >40 years at 49.23% (257 of total 522 cases). AUB was more common in Multipara at 61.49% (321 of 522 cases). Menorrhagia was commonest pattern in AUB accounting for 51.34% (268 of 522cases). Thyroid dysfunction was present in 12.27% (64 of 522) of cases with AUB. Among them hypothyroid was most common accounting for 8.81% (46 of 522 cases). Hyperthyroidism was present in 3.44% (18 of 522 cases). Menorrhagia was most common pattern in Hypothyroidism at 65.21% (30 of 46 cases, followed by polymenorrhea at 17.39% (8 of 46 cases). Oligomenorrhea was most common in hyperthyroid group at 55.54% (10 of 18 cases) closely followed by hypomenorrhea at 44.44% (8 of 18 cases). Conclusions: Abnormal uterine bleeding (AUB) is one of the commonest gynecological complaint at gynecological OPD. Thyroid dysfunction is noted consistently in cases of AUB. So, evaluation of thyroid profile should be part of evaluation of AUB, especially during perimenopause.